Exploring potential environmental drivers of migration phenology in two Mongolian Plateau-nesting goose species - Junjian Zhang; Xianghuang Li; Xueqin Deng; Iderbat Damba; Nyambayar Batbayar; Zhenggang Xu; Yong Zhang; Lei Cao; Anthony David Fox (Movement Ecology)
Abstract Background Migratory phenology affects fitness and therefore plays a crucial role in the annual life cycle of migrants. Various indicators in relation to the migration patterns of Arctic nesting birds have been well studied (e.g. vegetation production), but we still lack knowledge from lower latitudes, e.g. the Mongolian Plateau, which is one of the top-priority regions for avian research and conservation. Methods We used 208 spring and 248 autumn migration tracks from individually tagged Swan Geese Anser cygnoides (SG) and Greylag Geese A. anser (GG) from four geographically discrete breeding groups across the Mongolian Plateau. We analyzed the difference in their migratory timing, how they responded to nine environmental metrics as indicators of environmental change, and the probability of spring arrival and autumn departure. Results We found significant differences in spring and autumn departure times between species, yet their arrival times were similar, although the migration phenology of eastern nesting birds differed significantly from those in central and western Mongolia. Their spring migration followed the onset of daily temperature reaching 0 °C, but was not correlated with indices of plant green-up, which occurred behind them along their migration routes. The autumn departure phenology of SG exhibited stronger responses to 0 °C nighttime temperatures, while the GG responded more to 0 °C cumulative temperatures. Conclusions Two goose species follow behind the daily 0 °C and before the green-up of plants in spring, allowing the time of hatching of goslings to coincide with the plant growth peak, ensuring a predictable food supply for the nidifugous juveniles. Vegetation and snow metrics were not appropriate indicators to predict the migration process of either species, due to the lack of strong latitudinal gradients in plant growth and long-term snow cover.